2016
DOI: 10.3892/etm.2016.3037
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic performance of clinical indices and model scorings for acute-on-chronic liver failure: A study of 164 patients

Abstract: Abstract.The present study aimed to analyze the prognostic factors of acute-on-chronic liver failure (ACLF), with the perspective of an improved selection of optimal therapeutic schemes. A retrospective analysis was used to study 164 patients with ACLF hospitalized between 2010 and 2014 in a single center. Patients were divided into favorable and unfavorable groups, according to the treatment outcomes. General characteristics and clinical manifestations were analyzed to determine whether they would affect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Comparisons of the predictive abilities of the CTP, MELD, MELD-Na, iMELD and ALBI scoring systems for the prognosis of HBV-ACLF are rarely reported. Attempts to analyze the impact of clinical parameters and the combined prognostic abilities of these parameters on ACLF prognosis have provided inconsistent results due to differences in study subjects, study phases and follow-up periods 13 - 15 . The integration of general information, clinical indicators and a prognostic scoring system may better predict the short-term outcomes of patients with HBV-ACLF.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of the predictive abilities of the CTP, MELD, MELD-Na, iMELD and ALBI scoring systems for the prognosis of HBV-ACLF are rarely reported. Attempts to analyze the impact of clinical parameters and the combined prognostic abilities of these parameters on ACLF prognosis have provided inconsistent results due to differences in study subjects, study phases and follow-up periods 13 - 15 . The integration of general information, clinical indicators and a prognostic scoring system may better predict the short-term outcomes of patients with HBV-ACLF.…”
Section: Introductionmentioning
confidence: 99%
“…In the whole sample, 33% of the patients showed an altered PT/INR, without significant differences between the groups studied. The PT/INR, besides evaluating the blood coagulation factor, also assists in estimating risks for acute or chronic liver failure (26) . ALT and AST levels indicated greater proportion among patients superinfected with HDV.…”
Section: Discussionmentioning
confidence: 99%
“…MELD score has been shown to be a valid predictor of long-term survival in patients with cirrhosis, as well as other areas beyond end-stage liver disease such as variceal bleeding, fulminant hepatic failure, alcoholic hepatitis and hepatocellular carcinoma [ 18 22 ] However, its role as a prognostic scoring system for patients with ACLF is still disputed. Various studies have found that MELD score alone cannot predict the postoperative mortality or morbidity for patients with ACLF, indicating the necessity for an effective scoring system to determine which patients can benefit from liver transplantation [ 23 26 ] Despite this, evidence exists to suggest that MELD score may have some utility as a prognostic marker in ACLF. A Chinese modified MELD was found to reveal poor prognosis in pre-ACLF patients [ 27 ] The prognostic model identified 5 independent factors associated with survival among patients with pre-ACLF and ACLF: MELD score, age, hepatic encephalopathy, triglyceride level and platelet count.…”
Section: Clinical and Prognostic Factorsmentioning
confidence: 99%